49.5k views
3 votes
Explain how the quotient of powers was used to simplify this expression. 5^4/25=5^2

User Yogishaj
by
5.7k points

2 Answers

4 votes


\bf ~\hspace{7em}\textit{negative exponents} \\\\ a^(-n) \implies \cfrac{1}{a^n} ~\hspace{4.5em} a^n\implies \cfrac{1}{a^(-n)} ~\hspace{4.5em} \cfrac{a^n}{a^m}\implies a^na^(-m)\implies a^(n-m) \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ \cfrac{5^4}{25}\implies \cfrac{5^4}{5^2}\implies \cfrac{5^4}{1}\cdot \cfrac{1}{5^2}\implies 5^4\cdot 5^(-2)\implies 5^(4-2)\implies 5^2

User Christian George
by
5.7k points
2 votes

Answer: The quotient of powers was used because 25=5^2 which means that 5^4/25 is the same as 5^4/5^2. 5^4/5^2= 5^2. You can check your answer by simplifying 5^4 which is 625 and 5^2 which is 25, then divide the two which is 625/25 which equals 25 (or 5^2)

Explanation: